Peran Guru Pendidikan Agama Katolik dalam Meningkatkan Kreativitas Belajar Peserta Didik di Sekolah Dasar - Tibo, Paulinus; Halek Bere, Paulus; Tarigan, Thomas Natalisa (Sekolah Tinggi Agama Katolik Negeri Pontianak, 2024)
This research is focused on the role of teachers as one of the factors that influence student success. Professional teachers can foster and produce active and creative students so that they can produce students with high levels of learning creativity. To increase student creativity, teachers must understand the meaning of learning creativity in order to create a fun, active, and creative learning environment. The researcher used a qualitative approach. This research was conducted using observation, interview, and documentation, and the informants were Catholic religious education teachers, students, class teachers, and school principals. The data analysis process uses triangulation techniques and source triangulation. Based on the field findings, Catholic religious education teachers at SD Negeri 101856 Gunung Rintih have played their roles as educators, teachers, mentors, creativity boosters, and advisors able to foster better learning creativity among students. Students dare to perform in front of the class or ask questions when the teacher explains, as well as students who dare to take every learning risk and are active and creative in the school environment. Teachers are advised to continue to improve their roles professionally so that they can create a culture of quality learning in schools.